Using a rate equations approach to model World population trends. (February 2013) - Gonzalo, Julio A; Muñoz, Felix-Fernando; Santos, David J
According to UN data and projections, the World population will begin to decrease by the middle of this century. This paper uses rate equations (fully analogous to those employed in condensed matter physics) to simulate the time evolution of World population, making use of UN population data in the time interval 1900–2010, and to extrapolate the evolution of World population into the near future. This approach has not been used in economics and population dynamics. The simulation predicts a population decline by mid-century. The economic consequences of a population decline would be far reaching.